2014
DOI: 10.18632/oncotarget.1819
|View full text |Cite
|
Sign up to set email alerts
|

ΔNp63 isoform-mediated β-defensin family up-regulation is associated with (lymph)angiogenesis and poor prognosis in patients with squamous cell carcinoma

Abstract: Beside a role in normal development/differentiation, high p63 immunoreactivity is also frequently observed in squamous cell carcinoma (SCC). Due to the complexity of the gene, the role of each p63 isotype in tumorigenesis is still confusing. Constitutively produced or induced in inflammatory conditions, human beta-defensins (HβDs) are cationic peptides involved in host defenses against bacteria, viruses and fungi. Here, we investigated both the role of p63 proteins in the regulation of HβDs and the implication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 37 publications
(48 reference statements)
1
14
0
1
Order By: Relevance
“…Previous studies demonstrated that other α ‐defensins (HNP1–3) inhibit endothelial cell adhesion and migration . In contrast, β ‐defensins have some pro‐angiogenic abilities . In the current study, we showed that blood vessel outgrowth from aortic rings is inhibited under the influence of high doses of HD‐5.…”
Section: Discussionsupporting
confidence: 52%
“…Previous studies demonstrated that other α ‐defensins (HNP1–3) inhibit endothelial cell adhesion and migration . In contrast, β ‐defensins have some pro‐angiogenic abilities . In the current study, we showed that blood vessel outgrowth from aortic rings is inhibited under the influence of high doses of HD‐5.…”
Section: Discussionsupporting
confidence: 52%
“…Furthermore, reduced tumor cell proliferation (marked by Ki67) was observed in tumors from ΔNp63-KD HCC1806 cells and ΔNp63-KD SUM159 cells compared with control cells, suggesting that reduced proliferation may be responsible for reduced tumor growth in ΔNp63-KD cells (Supplemental Figure 5, G and H). Angiogenesis positively correlates with metastasis, and ΔNp63 promotes tumor angiogenesis in pediatric neuroblastoma, osteosarcoma, and squamous cell carcinoma (34)(35)(36). Therefore, we assessed the expression of CD31 and CD34, markers for angiogenesis, as well as smooth muscle actin (SMA) (37) in HCC1806 and SUM159 primary tumors.…”
Section: Resultsmentioning
confidence: 99%
“…TP63 is also an active gene involving tumorgenesis [33]. In squamous cell carcinoma (SCC), ΔNp63, the predominant isoform of TP63, its over-expression in vitro and in vivo could up-regulate human beta-defensin (HβD), thus promoting tumor angiogenesis in SCC microenvironment [34]. Importantly, RNA-seq study between the white earlobes and the red earlobes indicated that, TP63 was significantly down-regulated in white earlobes compared to that in red ones.…”
Section: Discussionmentioning
confidence: 99%